Simulation of real time tracking system using RFID technology to enhance quality activities in flexible manufacturing system - Al Hazza, Muataz Hazza Faizi; Adesta, Erry Yulian Triblas (Institute of Electrical and Electronics Engineering, Inc., 2017)
Flexible Manufacturing System (FMS) attracts industries to adopt it for its high productivity and flexibility. Recent improvement of FMS focuses on real-time tracking to ease planning, control and inspection to final product. One of the potential tools to be used in tracking, monitoring and controlling the final products is the Radio Frequency Identification (RFID) technology. Implementing RFID will lead to lower cost and high efficiency. This paper simulated a real-time tracking system using RFID technology to enhance and track the quality and inspection activities in FMS using Colored Petri Net (CPN) method. The proposed system suggests using RFID tags on base that carries the parts to be processed in the manufacturing system rather than putting the tag in the parts themselves. RFID Read/writes capability have been assumed in the model. Therefore, updating the data during the process will be adapted, such as reference number and updated status of part in further stages in the system. This gives a chance to use the base with tag again after accomplishing all required operations in the production system for other parts. Thus, this method helps to reduce the required cost for manufacturing. The simulation of the system using CPN tool shows that parts can be tracked successfully and provides more enhancements for production.